Kurikulum Berdaya Saing Bahasa Arab di Era Digital - Kholiq, Ilham Nur (Edu Journal Innovation in Learning and Education, 2025)
Digital change now asks Arabic graduates to master both classical and modern forms of the language while using tech tools for cross-cultural talks, data insight, and teamwork online. When course programs fail to keep pace, lessons lose relevance, job seekers appear less promising on world stages, and learner curiosity dwindles, so a fresh, competitive plan must be built without delay. An evidence-driven blueprint ties what stakeholders want to every program part and zeroes in on clear, testable signs of strength within the digital Arabic space. This study therefore confronts head-on the shortage of a working definition and broad model for a future-facing Arabic syllabus and the gaps in knowing what current courses really offer. A qualitative case-study design is used here to map step by step how such a vigorous, tech-ready curriculum can take shape. To gather trustworthy findings, the study mixed three data-gathering tools-observation, interviews, and document checks-then explored everything with Miles and Hubermans interactive steps. Results show that the competitive Arabic curriculum at uimsya pba in Blokagung, which fuses pesantren roots with national standards, sits at the programs heart. When this blend pairs with LMS, online TOAFL quizzes, and flipped classes, and is still grounded in halaqah and yellow book study, graduates shine in schools, halal ventures, and diplomatic roles. Yet for true impact the curriculum must evolve hand-in-hand with industry, as shown by MoU with the Arabic Language MGMP for the creation of digital resources and curricular model modifications that address the requirements to increase graduates' relevance in the Society 5.0 era.